2023
DOI: 10.21203/rs.3.rs-3149349/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The estimation of seismic hazards in Eastern Turkey and its surrounding area by statistical approaches

Abstract: In this study, a complete set of 19933 earthquake data in the depth range from 1 to 30 km from 12 December 1905 to 30 September 2022 was collected and analysed by using the Gutenberg–Richter (GR) earthquake frequency magnitude relationship approach to determine b-value and completeness magnitude (Mc). The size scaling b- and a-values for the overall catalogue were estimated as 0.82 ± 0.01 and 5.452, respectively. The Mc for the entire investigated region was estimated to be equal to 1.9. The observed low b-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…On the other hand, recent works (e.g., as Altinoglu and Polat [33]) report that the presence of a fractal structure in faults impacts the distribution of earthquake magnitudes and, therefore, the exponent b GR of the Gutenberg-Richter law. In the same aspect, Alam et al [34] demonstrated a correlation between the b GR value and the fractal dimension in seismic events.…”
mentioning
confidence: 99%
“…On the other hand, recent works (e.g., as Altinoglu and Polat [33]) report that the presence of a fractal structure in faults impacts the distribution of earthquake magnitudes and, therefore, the exponent b GR of the Gutenberg-Richter law. In the same aspect, Alam et al [34] demonstrated a correlation between the b GR value and the fractal dimension in seismic events.…”
mentioning
confidence: 99%